Distribution and Abundance of Family Orchidaceae in Gunung Stong State Park, Dabong, Kelantan - Ahmad Adham Abdul Aziz (2024)
The purpose of this study was to determine the distribution and abundance of Orchidaceae in Gunung Stong State Park (GSSP), Kelantan. The data was analysed using the Simpson and Shannon-Wiener indices, and GIS was used for additional geographical analysis. According to the research, the study region contained 34 Orchidaceae species, of which 12 were found to belong to 6 genera collected at this area along the trails from the elevation 100m until 600m. Simpson's Diversity Index (D) was 0.906, while the Shannon-Wiener Diversity Index (H') was 2.262. These data show the abundance and distribution of Orchidaceae in GSSP. The study'sfindings confirm the necessity of Orchidcaeae conservation at the GSSP site.